1999
DOI: 10.1126/science.286.5437.120
|View full text |Cite
|
Sign up to set email alerts
|

Protamine-Induced Condensation and Decondensation of the Same DNA Molecule

Abstract: The DNA in sperm and certain viruses is condensed by arginine-rich proteins into toroidal subunits, a form of packaging that inactivates their entire genome. Individual DNA molecules were manipulated with an optical trap to examine the kinetics of torus formation induced by the binding of protamine and a subset of its DNA binding domain, Arg6. Condensation and decondensation experiments with lambda-phage DNA show that toroid formation and stability are influenced by the number of arginine-rich anchoring domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
213
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(228 citation statements)
references
References 22 publications
(7 reference statements)
13
213
2
Order By: Relevance
“…They showed that DNA condenses continuously and linearly with time once the compaction process begins. [14][15][16][17] The results seemed to support the widely accepted opinion that the toroid is formed by continuously absorbing DNA to a primary loop randomly nucleated on DNA. The temporal resolution of the experiments was, however, relatively low.…”
supporting
confidence: 75%
“…They showed that DNA condenses continuously and linearly with time once the compaction process begins. [14][15][16][17] The results seemed to support the widely accepted opinion that the toroid is formed by continuously absorbing DNA to a primary loop randomly nucleated on DNA. The temporal resolution of the experiments was, however, relatively low.…”
supporting
confidence: 75%
“…Therefore the intensity of fluorescence is low in sperm as compared to fluorescence intensity of round spermatid [66][67][68].…”
Section: Basics Of Dna Integrity Assaysmentioning
confidence: 99%
“…Dox/Duplex was mixed with m-protamine at an optimal mass ratio of 14:17 to prepare a positively charged Dox-loaded complex 41 (Dox/Complex) ( Fig. 3a and Supplementary Fig.…”
mentioning
confidence: 99%